High Platelet Reactivity and Antiplatelet Therapy Resistance - Linden, Matthew D.; Tran, Huyen; Woods, Robyn; Tonkin, Andrew (Seminars in Thrombosis and Hemostasis, 2012)
The term resistance has been applied to interindividual variability in platelet reactivity during antiplatelet therapy or to thrombosis despite appropriate therapy. In particular “aspirin resistance” and “clopidogrel resistance” have been the subject of intense investigation for their association with poor cardiovascular outcomes. Several mechanisms have been investigated including resistance arising from poor bioavailability, especially in clopidogrel therapy as resulting from a loss of function variant in hepatic metabolism required for prodrug activation. A limitation of studies linking on-treatment reactivity and clinical outcome is that they have been performed in high-risk patients with recent atherothrombotic disease. On-treatment platelet reactivity correlates with acuity of recent atherothrombosis, and variability in pretreatment platelet function predicts on-treatment platelet function for both aspirin and clopidogrel. It is therefore likely that high on-treatment platelet function at the time of testing may often result from underlying platelet hyperreactivity related to acute atherothrombosis, rather than true pharmacological resistance. The association of high on-treatment platelet reactivity with poor clinical outcomes may therefore be attributed to variability in underlying burden of disease instead of, or in addition to, pharmacological resistance to antiplatelet therapy.
Keywords: aspirin resistance; clopidogrel resistance; platelet hyperreactivity; cardiovascular disease; antiplatelet therapy